PENGARUH SANKSI PERPAJAKAN, PEMERIKSAAN PAJAK, KEPATUHAN WAJIB PAJAK DAN KESADARAN WAJIB PAJAK TERHADAP PENERIMAAN PAJAK PENGHASILAN (Studi Kasus di Kantor Pelayanan Pajak Pratama Sukoharjo) - Prabowo, Didik; Harimurti, Fadjar; Sunarti, Sunarti (Universitas Slamet Riyadi, 2020)
The purpose of this research is to analyse the significance of taxation sanctions, tax checks, taxpayer compliance and taxpayer awareness on the acceptance of income tax at Sukoharjo Primary Tax Service office. The population in this study is a taxpayer of a personal person registered with the primary Tax Service office of Sukoharjo until August 2019. Sampling techniques use purposive sampling, with a sample count of 40 respondents. Data collection methods used: questionnaires and documentation. Technical analysis of data used for validity tests, reliability tests, classical assumption tests, and multiple linear regression analyses. The results of the study gained the conclusion that there was a significant positive influence on taxation sanctions on income tax revenues. There is a positive and significant influence on tax checks on income tax revenues. There is a significant positive influence of taxpayer compliance with income tax acceptance. There is a significant positive influence of taxpayer awareness towards income tax acceptance.